The Effects of Digital Marketing and E-WOM on Purchase Decisions in the Automotive Industry: The Mediating Role of Purchase Intention - Alkhansa, Muhammad Rafi; Saputro, Edy Purwo (Akuntansi dan Teknologi Informasi, 2026)
Purpose –The purpose of this study is to examine the effect of digital marketing and electronic word of mouth (E-WOM) on purchasing decisions in the automotive industry, with purchase intention as the mediating variable. Methods – A quantitative approach was applied in this study, with data collection through surveys conducted on automotive consumers participating in digital forums and marketplaces. The data obtained was analyzed using the Smart PLS 3 application to test the relationship between variables, both directly and indirectly. Findings - This study concludes that digital marketing has a positive effect on purchase intention, which ultimately increases purchase decisions. E-WOM has also been proven to have a significant positive effect on consumer purchase intention and purchase decisions, based on the credibility of reviews from other users as the main factor. In addition, purchase intention plays an important role as a link between digital marketing, E-WOM, and purchase decisions. Implications - This finding provides practical contributions for automotive companies to develop more optimal marketing strategies through digital platforms, as well as utilizing E-WOM to drive increased purchase interest so that consumers ultimately decide to buy the product. Originality - The novelty of this study lies in its comprehensive analysis of digital marketing, E-WOM, and purchase interest in relation to purchasing decisions, whereas previous studies tended to analyze these variables separately.